Letter: the need to reconsider the liver‐specific benefit of carvedilol. Issue 3 (8th July 2021) - He, Lu; Lou, Lianqing
LINKED CONTENT: This article is linked to McDowell et al paper. To view this article, visit https://doi.org/10.1111/apt.16189